TAFSSA-farmer focus group discussion report: Rajshahiand Rangpur Divisions, Bangladesh - Cheesman, Stephanie; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2022)
This brief describes the first farmer household consultations that were carried out in the process of determining which diversified cropping patterns should be implemented in the TAFSSA on-station and on-farm trails in Northern Bangladesh.